Psychometric Evaluation of Brief Reason for Living Inventory for Adolescents (BRFL-A) Instrument in the Indonesian Language - Veranita Pandia MD, PhD; Efi Fitriana PhD; Irvan Afriandi MD, DrPH; Fredrick Dermawan Purba PhD; Febrianti Santiardi Danasasmita MD; Abdullah Ichsan MD; Kent Pradana MD; Alfonso Haris Setia Santoso MD; Rita Engellia MD; Fithriani Salma Mardhiyah MD (SAGE Publishing, 2024)
Objectives. The Brief Reason for Living Inventory for Adolescents (BRFL-A) is used to assess protective factors against suicide in non-clinical settings. This study aimed to validate the psychometric properties of BRFL-A in Bahasa Indonesia. Methods. A total of 728 high-school and university students filled BRFL-A questionnaire and the results were analyzed. The reliability, content, convergent, discriminant, and factorial or construct validity, were investigated using content validity index Cronbach's Alpha, while content validity index (CVI), confirmatory factor analysis, and Pearson product-moment correlation were assesed with MSPSS, SIS, INQ-15, and DASS-18. Results. The results showed that the Indonesian version of BRFL-A had good internal consistency, test-retest reliability, as well as content and concurrent validity, supporting both the 1-factor and the 5-factor model of factorial validity. Conclusions. The Indonesian version of the BRFL-A was valid and reliable to measure protective factors against suicide risk among adolescents and young adults in non-clinical settings.